Transitional Justice and Democratic Consolidation in the Post-Communist Space: A Comparative Review of the Czech Republic, Latvia and Slovakia - Sairambay Yerkebulan (Sciendo, 2021)
In this comparative review, I first evaluate scholarly findings attempting to dis/prove a relationship between transitional justice and the consolidation of democracy. Second, I outline several criteria for ‘democratic’ transitional justice in order to be able to judge transitional justice policies. Third, I examine and judge transitional justice policies of the Czech Republic, Latvia and Slovakia by these criteria. Last, I argue that transitional justice is neither a prerequisite for the successful consolidation of democracy nor inherently democratic unless it is carried out in coordination with the ideals of liberal democracy, which might support the achievement of peace and societal stability in a transition period.